Investigations on spider house for anti microbial activity - Mirghani, Mohamed Elwathig Saeed; Zulkifli, Mohamad Zul Fahmi (IIUM Press, 2011)
The purpose of this new investigation was to determine if spider webs exhibit antibacterial properties. In order to determine antibacterial properties, the spider webs were extracted with different solvents such as methanol, ethanol, acetone, and water in different conditions (extraction time, and concentration used for optimization). These extracts were screened for antibacterial activity using disc diffusion assay. Two bacteria were used in the antibacterial assay namely Bacillus subrilis, and Escherichia coli The determination of spider webs exhibiting antibacterial properties was based, at least in this study, solely upon the definite appearance of an inhibition zone around the well of plates. In screening, acetone solvent was shown the best antibacterial activity compare to other solvents with 10 mm of diameter of inhibition zone for Bacillus subtilis and 9 mm of diameter of inhibition zone for Escherichia coli. In optimization, the maximum inhibition zone on the Bacillus subtilis was 15 rom at a time of 48 hours and concentration of 0.035 g/ml. Meanwhile, the maximum diameter of inhibition zone on the Escherichia coli was 12 mm at a time of 48 hours and concentration of 0.035 g/ml. Therefore, this study showed that spider webs could be potential source of new antibacterial agents.